2014
DOI: 10.1007/s10544-014-9890-0
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo characterization of wireless and passive micro system enabling gastrointestinal pressure monitoring

Abstract: This paper presents a wireless and passive micro pressure system based on the LC mutual inductance detection mechanism for gastrointestinal (GI) pressure monitoring. The micro pressure system is composed of a sensor capsule (a pressure sensitive micro capacitive sensor in series with an induction coil to form an LC tank) and a detection unit (a detection coil connected with a network analyzer). The pressure variations under measurement lead to changes in the capacitance of the pressure sensor and therefore a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The system works without batteries and electrical components for energy transfer. The functionality of the system is confirmed by in-vivo and invitro experiments [36].…”
Section: Microrobots In Medicinementioning
confidence: 67%
See 2 more Smart Citations
“…The system works without batteries and electrical components for energy transfer. The functionality of the system is confirmed by in-vivo and invitro experiments [36].…”
Section: Microrobots In Medicinementioning
confidence: 67%
“…Several studies have also reported using a microrobot for endoscopy [27,28,36,37]. For instance, Iddan et al [27] reported a study presenting a new painless endoscopic imaging of the small bowel.…”
Section: Microrobots In Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…WMC for use in whole-gut transit was validated using dogs 109 and has been used in several studies in dogs, 110 , 111 , 112 pigs, 113 rabbits, 114 and horses. 115 To our knowledge, validated technologies have not been developed for use in small animals.…”
Section: Whole-gut Transit In Preclinical Modelsmentioning
confidence: 99%
“…In 2014, Professor J.B. Wang proposed a new differential transduction circuit based on the LC mutual inductance detection mechanism for gastrointestinal pressure monitoring, which is composed of a sensor capsule and a detection unit. The micro-pressure system can realize long-term monitoring stability, and the sensitivity can reach up to 0.2491 kHz/kPa [ 34 , 35 , 36 ].…”
Section: Research Status Of Wireless Passive Lc Sensors For Harsh mentioning
confidence: 99%